1995
DOI: 10.1159/000106930
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality and Institutionalization in Alzheimer Disease Patients 1 Year after Discharge from an Alzheimer Dementia Unit

Abstract: Several factors have been reported to predict death and institutionalization in demented patients, even if the results of the studies are often conflicting. We conducted a study on a group of 86 consecutive noninstitutionalized probable Alzheimer disease (AD) patients, to evaluate clinical and social factors predicting mortality and institutionalization 1 year after discharge from the Alzheimer Dementia Unit at ''Sacro Cuore Fatebenefratelli’ Hospital, Brescia, Italy. The 1-year mortality rate was 13.9% and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 21 publications
4
84
0
Order By: Relevance
“…Use of home health services has been strongly associated with impairment in ADL, but not in cognition, among care recipients with AD [43] and thus might serve as an indicator of a loss of functional capacities, an important predictor of increased mortality in dementia [44,45]. Consistently, we observed that deterioration in basic ADL was an independent predictor of shorter survival in the multivariate models.…”
Section: Discussionsupporting
confidence: 83%
“…Use of home health services has been strongly associated with impairment in ADL, but not in cognition, among care recipients with AD [43] and thus might serve as an indicator of a loss of functional capacities, an important predictor of increased mortality in dementia [44,45]. Consistently, we observed that deterioration in basic ADL was an independent predictor of shorter survival in the multivariate models.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, when patients with long-term neurological illnesses have disrupted sleep, this becomes a problem not only for the patient but also for their carers (Bianchetti et al, 1995;Van Someren, 2000). The pronounced increase in nighttime activity of both carers and HD patients suggests that more attention should be paid to the management of the sleep disorder in HD.…”
Section: Discussionmentioning
confidence: 99%
“…When patients with long-term neurological illnesses have disrupted sleep, this becomes a problem not only for the patient but also for their carers (Bianchetti et al, 1995;Van Someren, 2000). Identification of its origin is essential to rational management of these diseases and should also provide novel insights into the nature of the neurodegenerative process.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in our opinion, treating disrupted sleep in long-term neurologically ill patients is important, because a quiet night sleep for the patient would also benefit the patient's partner or the caregiver. In Alzheimer's disease, the sleep disturbances are a major factor for decision of institutionalization of the patients (Bianchetti et al, 1995;Hatfield et al, 2004). Thus, in HD, focused management of disturbed sleep may also mean the postponement of the institutionalization of HD patients.…”
Section: Discussionmentioning
confidence: 99%